Laparoscopic adjustable gastric band removal and outcome of subsequent revisional bariatric procedures: A retrospective review of 214 consecutive patients. (March 2016) - Kirshtein, Boris; Kirshtein, Anna; Perry, Zvi; Ovnat, Amnon; Lantsberg, Leonid; Avinoach, Eliezer; Mizrahi, Solly
Abstract: Background: Laparoscopic adjustable gastric band (LAGB) removal is required in cases of slippage, erosion, infection, intolerance, or failure in weight loss. The aim of the study was to follow up the patients who underwent band removal and analyze the outcome of subsequent revisional bariatric procedures. Patients and methods: A retrospective review of consecutive patients who underwent LAGB removal during 3.5 years. All patients underwent a phone interview in early 2015. Patients were divided to three groups following band removal: without additional surgery, laparoscopic sleeve gastrectomy (LSG) or laparoscopic Roux-en Y gastric bypass (LRYGB), and Redo LAGB(Re-LAGB). Outcome of different revisional procedures was compared according to causes and symptoms before band removal, patient satisfaction, weight loss, quality of life (QOL) questionnaire, and the bariatric analysis and reporting outcome system II (BAROSII) score. Results: Overall 214 patients (73.8% females) with mean age of 41.9 years were enrolled in the study. The mean time between LAGB placement and removal was 81.0 months. Mean % estimated weight loss (%EWL) was 29.6 at time of band removal. There was no difference between groups in patient age, gender, BMI before LAGB, and most co-morbidities. Patients with 1–5 outpatient visits preferred additional surgery. Patients suffering from vomiting from 1 to 10 times per week preferred revision as LSG or LRYGB. Patients with lower BAROS score underwent LSG or LRYGB. Most of the patients with band intolerance underwent conversion to another bariatric procedure, while patients with band erosion and infected band preferred Re-LAGB. Most of the patients without band gained weight. There was a significant improvement in %EWL (39.9 vs 29.6), QOL (1.08 vs 0.07), and BAROS(2.82 vs-0.11) in patients who underwent additional bariatric surgery before and after band removal irrespective of surgery type. Conclusions: Patient selection for different revisional bariatric procedures after LAGB removal is a main point for surgery success. This results in high patient satisfaction, EWL, and QOL. All options (Re-LAGB, LSG, LRYGB) are feasible and safe. Highlights: Simple band removal without additional bariatric surgery results in weight gain. Re-LAGB is successful in patients with good weight loss and high QOL after primary LAGB. Patients with low QOL and weight loss following LAGB required another bariatric procedure.